Enhancing the Student’s Writing Skills of Procedure Text by Using Storyboarding at the Seventh Grade Students of Junior High School 53 Palembang - Hendro Setiawan; Syafruddin .; Farnia Sari (Jurnal Didascein Bahasa, 2015)
ABSTRACT: The research aimed to find out the effectiveness in teaching writing of procedure text by using storyboard to the seventh grade students at State of Junior High School 53 Palembang in the academic year 2014/2015. The sample was the class of VII.1, consisted of 30 students. The method used in this research was pre-experimental method, with pre-test and post-test design. The data were obtained by means of the test and the results were analyzed through paired sample t-test calculation. Based on the result, the mean or average of pre-test was 11.93, the standard deviation was 3.754, and the standard error mean was 0.685. The mean or average of post-test was 18.47, the standard deviation was 3.277, the standard error mean was 0.598 and the writer got the t-obtained 10.640. It showed that t-obtained was higher than critical value (2.045). It can be concluded that it is effective using storyboard in teaching writing of procedure text to the seventh grade students at State of Junior High School 53 Palembang.Key words: writing skill, procedure text, storyboarding